Quantitative temperature and relative humidity changes recorded by the Lake Cuoqia in the southeastern Tibetan Plateau during the past 300 years - Yan, Tianlong; Zhang, Can; Zhang, Haixia; Sun, Xiaoshuang; Liu, Yilan; Liu, Ruikun; Zhang, Wei; Zhao, Cheng (Frontiers in Ecology and Evolution, 2023)
High-elevation lakes on the Tibetan Plateau have the advantage of sensitive response to climate changes. Multiple proxy records in lake sediments can provide a large amount of extractable information for paleoclimate reconstructions and assessing the position of recent global warming within the context of natural climate variability. In this study, we reconstruct the climatic and environmental changes over the past 300 years from a remote alpine lake (Lake Cuoqia) in the southeastern Tibetan Plateau using multiple proxies including branched glycerol dialkyl glycerol tetraethers (brGDGTs), n-alkanes, elements, fatty acids and their hydrogen isotopes. Due to ice-cover nature of lake surface during winter, brGDGTs mainly reflect the variation in warm-season temperature from March to October, supported by nearby instrumental data. Our reconstructed high-resolution temperature showed a continuous cooling trend between 1700 and 1950 AD, followed by a rapid warming afterward, in parallel with other proxies such as n-alkanes and fatty acids in the same core, which is also consistent with previously published regional temperature records. The hydrogen isotope (δD) of fatty acids, similar to regional tree-ring δ18O, can record the history of atmospheric precipitation isotope and further indicate the variations of regional relative humidity. Our record exhibited a long-term decrease since 1700 AD, in accord with the decreasing lake level inferred from the ratio of Fe/Mn. The combined pattern of reconstructed temperature and relative humidity showed consistent changes before 1950 AD toward to a gradually cold-dry trend, whereas started to decouple afterward. Before 1950 AD, the declined temperature and relative humidity are mainly driven by insolation and thermal contrast between the Indian-Pacific Ocean and south Asian continent. After 1950 AD, decoupling of temperature and relative humidity may be related to the increased regional evaporation and human-induced emission of greenhouse gases and aerosol.